AB0441 Drug survival and reason for drop-out in rheumatoid arthritis patients with a non-medical switch from originator to biosimilar etanercept – preliminary data from a norwegian multicenter study. (12th June 2018) - Haugeberg, G.; Bakland, G.; Rødevand, E.; Fevang, B.T.; Hansen, I.J.W.; Diamantopoulos, A.
Abstract : Background: Norwegian rheumatologists are encouraged to prescribe the lowest-priced biologic DMARDs according to the national tender system. Thus, non-medical switch from the originator drug to its biosimilar is extensively performed. There is a need for more real life data to clarify the clinical outcomes, dropout rates and reasons for these dropouts after a non-medical switch from the originator to biosimilar ETN. Objectives: To explore drug survival and clinical outcomes in rheumatoid arthritis (RA) patients after a non-medical switch from the originator to biosimilar ETN (SB4) in ordinary outpatient clinics across Norway. Methods: Herein we present preliminary data collected at one participating centre. Patients were monitored and data were collected by the use of a hospital clinical computer system GoTreatIT Rheuma. The computer system is also used for data collection for the Norwegian national arthritis registry, NorArtritt. Demographic, clinical and treatment data were retrieved (21st of January 2018) from the computer system for the time point of non-medical switch of ETN and the last follow up. Wilcoxon matched-pair signed rank test was used for comparison between the two-time points. Results: Since April 2016 191 RA patients (mean age 60.8 years, 67% females) underwent a non-medical switch from originator to biosimilar ETN. Mean (SD) observation time for the 163 patients (85.3%) still on biosimilar ETN was 1.23 (0.46) yrs. 28 patients (14.7%) stopped treatment. Among them mean (SD) observation time for the 7 patients (3.7%) in remission was 0.53 (0.33) yrs, for the 10 patients (5.2%) reporting adverse events 0.44 (0.32) yrs and for the 11 patients (5.8%) reporting lack or loss of efficacy 0.44 (0.35) yrs. The adverse events reported was: 1 chest pain, 1 neuropathy, 1 GI reaction, 1 visual impairment, 1 infection, 2 joint stiffness (1 patient went back on ETN SB4) and 3 skin reactions. For all 191 patients no significant change (median [IQR]) from baseline to last observation was seen for DAS28 (2.1 [1.5–2.8] vs 1.9 [1.5–2.5], p=0.33), MHAQ (0.3 [0.0–0.7] vs 0.4 [0.1–0.6], p=0.62) and patient VAS global (20.0 [10.0–43.0] vs 25.0 [10.0–43.3] mm, p=0.73), whereas CRP improved significantly during follow up (2.0 [1.0–5.0] vs 1.0 [1.0–5.5] mg/dl, p=0.02). For the subgroup of RA patients who stopped treatment because of lack of efficacy a minor non-significant impairment was observed for DAS28 (2.0 [1.4–2.5] vs 2.6 [1.2–4.0], p=0.32), CRP (0.0 [0.0–6.0] vs 3.5 [0.8–13.3] mg/dl, p=0.66), MHAQ (0.1 [0.0–0.1] vs 0.5 [0.3–0.5], p=0.66) and patient VAS global (20.0 [10.0–30.0] vs 29.0 [17.0–58.5] mm, p=0.66). Conclusions: Our preliminary data indicate that for the majority of patients, a non-medical switch from originator to biosimilar ETN (SB4) was well tolerated with no impairment in disease measures. Whether the reported adverse events were associated to the switch needs to be further studied. In patients who stopped the biosimilar because of lack of effect only a minor numerically increase in disease measures was seen. Our promising preliminary results need to be confirmed in a large scale study. Disclosure of Interest: G. Haugeberg Shareholder of: DiaGraphIT AS, G. Bakland: None declared, E. Rødevand: None declared, B. T. Fevang: None declared, I. J. Hansen: None declared, A. Diamantopoulos: None declared